Edaphic fauna and its relations with chemical, physical and microbiological attributes in Araucaria forest - Pereira, Jamil de Morais (2020)
The permanent plant cover of the soil, in Araucaria forests, contributes to the conservation of the soil biodiversity. The aim of this study was to evaluate the potential of the soil fauna in discriminating native and reforested Araucaria forests. Native (NF) and reforested (RF) Araucaria angustifolia forests were evaluated in three regions of the state of São Paulo, representing three true replicates. In each area, fifteen soil samples were collected for the evaluation of the physical, chemical, and microbiological attributes and at the same points, the fauna was collected, using pitfall traps. The soil fauna was influenced by seasonality, presenting greater abundance of individuals in the summer. Collembola, Formicidae and Coleoptera groups were the most abundant ones, independently of the sampling season and the forest type. The Principal Component Analysis (PCA) and Canonical Discriminant Analysis (CDA) clearly differentiated native or reforested Araucaria areas. In PCA, Hemiptera, Collembola and Diplopoda were associated with RF in the winter, mainly due to the higher litter dry mass values. In NF, Orthoptera, Hymenoptera, Araneae and Coleoptera groups were explained by the higher quality of soil and litter, which was associated with NF. In summer, the groups Hemiptera, Orthoptera, Araneae, Coleoptera and Collembola, associated with NF, were explained by the higher values of microbial biomass carbon, Ca, P, organic carbon, macroporosity and dehydrogenase activity. In the CDA, the abundance of taxonomic groups was the most important attribute of the soil fauna for the discrimination of the forests. Likewise, soil moisture, soil P content, total porosity, and sulfur content of the surface litter contributed to discrimination between forests. There was some similarity between areas regarding certain groups of soil fauna, which we suggest being a result of the stability reached by the reforested areas, rendering them somewhat similar to the native ones.